Effect of Aluminum Powder Content on Air Blast Performance of RDX-Based Explosive Grenade Charge - Kun Zhang; Xuesong Feng; Juan Zhao; Bo Feng; Xiao jun Feng; Xiaofeng Wang (Advances in Materials Science and Engineering)
For aluminized explosive, the charge performance of explosive grenade is very significant for promoting their application. Firstly, the detonation performance of cyclotrimethylenetrinitramine (RDX) based explosives with different aluminum powder (0%, 20%, 25%, 30%, 35%, and 40%, respectively) content was investigated. Next, the air blast tests of RDX-based aluminized explosives were carried out. Then, RDX-based explosive grenade charges of L-1 and L-2 where the aluminum powder content was 20% and 25% were selected for air blast and static blasting fragments velocity tests. Finally, the energy release mechanism of the air blast was deduced via calculation. The results show that RDX-based aluminized explosives have higher detonation heat, detonation velocity, and detonation volume when the aluminum powder content is 20%, and the shock wave over pressure as well as impulse keep a high level at the same time within 4.5 m. The air blast performance of L-1 is better than L-2 within 2.2 m. As the distance increases, the air blast energy of L-1 is mainly used for shell rupture and fragment acceleration, while the contribution of L-2 is less than that of L-1. This study demonstrated that the explosion power of RDX-based explosive grenade charge is the most powerful where the content of aluminum powder is about 20%.